BIOLOGICAL ACTIVITIES OF TYPHA CAPENSIS (TYPHACEAE) FROM LIMPOPO PROVINCE (SOUTH AFRICA) - Masoko, P.; Mokgotho, M. P.; Howard, R. L.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Dried ground leaves and rhizomes of Typha capensis were extracted with different solvents of varying polarity (hexane, dichloromethane, acetone, methanol) to determine the best extractant for subsequent isolation and characterization of antibacterial compounds. Some extracts were active against Escherichia coli and Enterococcus faecalis, with at least one of them exhibiting minimum inhibitory concentration value of 0.04 mg/ml. Methanol was the best extractant with an average minimum inhibitory concentration (MIC) value of 0.75 mg/ml (rhizome) and 0.21 mg/ml (leaves) for the four pathogens. Escherichia coli and E. faecalis were the most sensitive with the average MIC values of 0.53 and 0.42 mg/ml, respectively. Staphylococcus aureus was the most resistant pathogen. The MIC values for the positive control (ampicillin) were ranging from 0.08 mg/ml to 0.16 mg/ml. Average total activity, a measure of potency, was highest for methanol (4498 ml/g) leaves and (1838 ml/g) rhizomes extract followed by acetone (1795 ml/g) leaves and (1075 ml/g) rhizome extracts. The most active compounds were at the Rf value of 0.47 against all pathogens. In some extracts the antibacterial activity was high enough to consider extracts for isolation and characterization of antibacterial compounds.Acknowledgements: The National Research Foundation (NRF) and Department of Biochemistry, Microbiology and Biotechnology, University of Limpopo provided financial assistance.